Hubungan Organizational Citizenship Behaviour (OCB) Dan Motivasi Kerja Dengan Kinerja Karyawan. - Ruth Damayanti; M. Rajab Lubis; Sjahril Effendy (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2020)
This study aims to determine the organizational citizenship behavior (OCBC) correlation and work motivation with the performance of CV employees. Bagus Alam Sejahtera, Medan. The sampling technique in this study was total sampling. The sample in this study amounted to 100 people. The instrument used was a Likert scale questionnaire. The data collection technique uses three scales consisting of organizational citizenship behavior (OCB), work motivation, and employee performance. The data analysis technique used is Multiple Regression. Based on the results of the study concluded that: 1) There is a significant correlation between organizational citizenship behavior (OCBC) with employee performance with a correlation coefficient (rx1y) of 0.736 with p = 0,000, and r2 = 0.542 with a contribution of 54.2%. 2) There is a significant correlation between work motivation and employee performance with a correlation coefficient (rx2y) of 0.632 with p = 0,000, and r2 = 0.400 with a contribution of 40.0%. 3) There is a significant correlation between organizational citizenship behavior and work motivation together with employee performance, this result is indicated by the linear coefficient value F = 76,386 and p = 0,000, p 0,05 and r2 = 0,612, with a contribution of 61 , 2%. These results indicate that there are still 39.2% contributions from other factors that can affect employee performance. From these results it can be said that the higher organizational citizenship behavior and work motivation, the higher the employee's performance, and conversely the lower the organizational citizenship behavior and work motivation, the lower the employee's performance.